2020
DOI: 10.3389/fpls.2020.540894
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Polyploidy in Grafted Crops

Abstract: Synthetic polyploids have been extensively studied for breeding in the last decade. However, the use of such genotypes at the agronomical level is still limited. Polyploidization is known to modify certain plant phenotypes, while leaving most of the fundamental characteristics apparently untouched. For this reason, polyploid breeding can be very useful for improving specific traits of crop varieties, such as quality, yield, or environmental adaptation. Nevertheless, the mechanisms that underlie polyploidy-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 224 publications
(299 reference statements)
3
43
0
7
Order By: Relevance
“…cerasiformis ). These genotypes were classified as susceptible (CER3) or extremely susceptible (MAR1, CER1) to V. dahliae despite being polyploid genotypes, a characteristic previously related to resistance to abiotic and biotic stress in plants ( Sattler et al, 2016 ; Ruiz et al, 2020 ; Russo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…cerasiformis ). These genotypes were classified as susceptible (CER3) or extremely susceptible (MAR1, CER1) to V. dahliae despite being polyploid genotypes, a characteristic previously related to resistance to abiotic and biotic stress in plants ( Sattler et al, 2016 ; Ruiz et al, 2020 ; Russo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, tetraploid leaves showed a higher elastic modulus, a parameter that describes the relationship between turgor and cell volume and reflects foliar cell rigidity (Barlett et al, 2012;Trifilo et al, 2016;Nadal et al, 2019). If stomatal closure is linked to the turgor loss point, a higher elastic modulus may be useful during periods of water scarcity, extending the time in which water is retained in the leaves compared with diploids, as observed, for example, in polyploid rootstocks (for a review see Ruiz et al, 2020). Pressurevolume relationships have been extensively used in the study of leaf and stem hydraulic properties of woody species (Sack et al 2003;Nadal et al, 2019), but rarely comparing conspecific individuals with different ploidies, such as in seedlings of Betula, which also exhibited a higher water content at turgor loss for tetraploids (Li et al, 1996).…”
Section: Enhanced Leaf Hydration and Water Retention In Tetraploidsmentioning
confidence: 99%
“…Polyploidy is often associated with a wide range of morphological and physiological changes that may be advantageous under harsh environments (Brochmann et al, 2004). Indeed, several investigations have shown that polyploidization improves stress tolerance under adverse environmental conditions (for review, see Ruiz et al, 2020), which remains true in woody grafted plant species (Khalid et al, 2020;Ruiz et al, 2020). Most citrus are diploid, and several citrus species produce apomictic seeds favoring the natural occurrence of polyploidy among seedlings (Aleza et al, 2011).…”
mentioning
confidence: 99%